Effects of aging on whole-body center of mass movement and lower limb joint kinematics and kinetics during deep-squat movement. (March 2022) - Honda, Keita; Sekiguchi, Yusuke; Shimazaki, Satoko; Suzuki, Rie; Suzuki, Takahiro; Kanetaka, Hiroyasu; Izumi, Shin-Ichi
Abstract: Deep-squat movement is one of the most important activities for independent living. Although a large range of motion of lower extremity joints in the sagittal plane is required for deep-squat movement, older individuals exhibit reduced mobility of lower limb joints. However, the effect of aging on deep-squat movement remains unclear. The purpose of this study was to investigate the age-related changes in the whole-body movement and lower extremity joint kinematics and kinetics during deep-squat movement. Twelve older and nineteen younger individuals performed the deep-squat movement, with knee flexion exceeding 100 degrees, and a motion analysis system and force plates collected their motion data. The median (interquartile range) age of older and younger individuals was 76.5 (3.3) and 30.0 (9.0) years, respectively. The deep-squat depth was significantly shallower in older individuals than in younger individuals ( P  < 0.05). Furthermore, older individuals exhibited smaller ankle dorsiflexion and knee flexion angles, larger trunk flexion angles, and greater forward displacement of the whole-body center of mass during deep-squat movement ( P  < 0.05). In terms of kinetic variables, older individuals exhibited smaller contributions of knee extension moment and larger contributions of hip extension moment to the support moment in the timing of the maximum support moment during deep-squat movement ( P  < 0.05). Our results indicated that older individuals have greater difficulty with deeper-squat movement and smaller contribution of knee extension moment to support body weight using trunk, hip, and ankle movements during deep-squat movement.